2020
DOI: 10.1016/j.carbpol.2019.115741
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of bile salts with a dietary fibre, methylcellulose, and impact on lipolysis

Abstract: Highlights BS, NaTC and NaTDC, impact the rheological properties and gelation of MC.  NaTDC has a greater impact on the viscoelasticity of MC compared to NaTC. NaTDC desorbs from a MC-stabilised interface at lower concentrations than NaTC. Upon digestion, NaTDC destabilises more readily MC-stabilised emulsion droplets. During MC-stabilised emulsion digestion, NaTDC generates less FFA than NaTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(75 reference statements)
2
6
0
Order By: Relevance
“…( B ) Statistical significance was calculated by using the t-sample t-test. The magnitude of the %FFA is in line with results from other researchers who also digested sunflower oil/WPI, or other protein emulsions, with similar emulsion sizes [ 64 , 65 , 67 ]. p < 0.0001 indicates that the values are statistically significant.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…( B ) Statistical significance was calculated by using the t-sample t-test. The magnitude of the %FFA is in line with results from other researchers who also digested sunflower oil/WPI, or other protein emulsions, with similar emulsion sizes [ 64 , 65 , 67 ]. p < 0.0001 indicates that the values are statistically significant.…”
Section: Figuresupporting
confidence: 89%
“…(B) Statistical significance was calculated by using the t-sample t-Figure 8. (A) FFA released over time from WPI-stabilized emulsion in respect to two different forms of BS: NaTC and NaDC at 10mM under physiological conditions at 310.15 K. Experimental results of CMC of NaTC and NaDC at 310.15 K with errors are also shown.The CMC of NaTC and NaDC have been shown to be statistically significant, p < 0.0001, and are comparable to previously determined values (5-20% of FFA after 60 min for NaTC and NaTDC at 10 mM and 50 mM, methylcellulose stabilized emulsion[64], 10-13% of FFA after 60 min for mix BS at 9.7 mM, WPI-stabilized emulsion [65], 6.5-15% of FFA after 60 min. for mix BS at 10 mM[66].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Sequestration (also referred to as binding) is another mechanism that can lead to decreased bioaccessibility of nutrients. Sequestration can occur at different length scales: interaction with solubilized polysaccharides (e.g., β-glucan and arabinoxylan) and entrapment of digestive agents or substrates into particulates or porous network [81][82][83][84]. At the molecular level, the structural and physicochemical features of the polysaccharides, particularly their charge, hydrophobicity and hydrophilicity, affect their ability to interact with other compounds.…”
Section: Sequestrationmentioning
confidence: 99%
“…3 In contrast, plant-based products, as well as edible mushrooms, being rich in fibre and low in saturated fat, [4][5][6] could help in the prevention of coronary heart disease and stroke by reducing blood lipid levels. 7,8 There is now accumulating evidence that MYC-based products can elicit similar beneficial effects on blood lipids. For instance, a study by Turnbull et al 9 reported improvements in blood lipid profiles (e.g., lower total cholesterol and low-density lipoprotein cholesterol (LDL) and higher high-density lipoprotein cholesterol (HDL) levels) in participants with slightly raised cholesterol levels following a MYC enriched-diet (three weeks) when compared to a meat-based diet (type not disclosed).…”
Section: Introductionmentioning
confidence: 99%